Global Burden and Changing Trend of Hepatitis C Virus Infection in HIV-Positive and HIV-Negative MSM: A Systematic Review and Meta-Analysis - Zheng, Yang; Ying, Meike; Zhou, Yuqing; Lin, Yushi; Ren, Jingjing; Wu, Jie (Frontiers in Medicine, 2021)
Background: The disease burden on hepatitis C virus (HCV) infection in human immunodeficiency virus (HIV)-positive and -negative men who have sex with men (MSM) is changing. We aim to provide an updated comprehensive estimate of HCV prevalence and incidence among the HIV-positive and -negative MSM population at the country, regional, and global levels as well as their changing trends over time. Methods: PubMed, Embase, PsycINFO, CINAHL, and conference databases were searched, and eligible records on the prevalence and incidence of HCV antibodies were selected and pooled via a random-effects model. Meta-regression was performed to demonstrate the association between the pooled rates and study year. Results: A total of 230 articles reporting 245 records from 51 countries with 445,883 participants and 704,249 follow-up person year were included. The pooled prevalence of HCV in MSM was 5.9% (95% CI, 5.1-6.8%), with substantial differences between countries and regions. Low- and lower-middle-income countries (12.3%, 7.0%) manifested a larger disease burden than high- and upper-middle-income countries (5.8%, 3.8%). HCV prevalence in HIV-positive MSM was substantially higher than in HIV-negative MSM (8.1% vs. 2.8%, p<0.001). The pooled incidence of HCV was 8.6 (95% CI, 7.2-10.0) per 1000 person-years, with an increasing trend over time, according to meta-regression (p<0.05). Conclusion: Global HCV prevalence in MSM varies by region and HIV status. Behavior counseling and regular HCV monitoring are needed in HIV-positive subgroups and high-risk regions. Given the upward trend of HCV incidence and sexual risk behaviors, there is also a continued need to reinforce risk-reduction intervention.